Analisis Kinerja Keuangan Pada PT. Sandhy Putra Makmur Perwakilan Pontianak - Dedy Hariyanto; Fitriana S (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of this study was to conduct an analysis of the financial performance on PT.Sandhy Putra Makmur, Representative Pontianak. Type of research is descriptive research with data collection consists of primary data that includes interviews and observations; and secondary data by studying the documentation of the records or documents from PT. Shandy Putra Makmur Representative Pontianak.Alat analysis used is Selling Relative Value Analysis and Analysis of Financial Performance Ratio consisting of Ratio Analysis Liquidity, Solvency Ratios, Profitability Ratios, and Activity Ratios. The results of this study indicate that: Selling Nijai Analysis Relative to the field of business Building Management, Network Cabling, Security Guard Business / TLH, Mechanical Electric, General Trading Enterprises, and business fields PSB / IKR / IKG experiencing fluctuating percentage relative sales value. Then on Liquidity Analysis consisting of Current Ratio and Quick Ratio has a very good ratio number of criteria, while Cash Ratio indicates the criteria is not good. In Solvency analysis consisting of Total Debt to Total Assets Ratio figures show the average ratio on standard criteria quite well, while on the Net Worth to Total Debt Ratio figures show the average ratio is less good on the standard criteria. In Profitability Analysis consisting of economic profitability and equity capital profitability ratio that is the ratio of the numbers in accordance with the standards and represents an average of the criteria very well. In the analysis of activity that consists of asset turnover ratio and working capital turnover ratio indicates the ratio in accordance with the standards and represents an average of both criteria.